A prototype of developing alumni portal for FTMSK, UiTM / Hanim Yahaya - Yahaya, Hanim (Faculty of Information Technology and Quantitative Sciences, 2005)
This project is developing a prototype on alumni portal for one of the faculty in UiTM that is Faculty of Information Technology and Science Quantitative. Currently the faculty faced a problem on how to keep in touch with their graduate student. As for solving this problem, portal for alumni need to build as the objective is to create a prototype of a "middle person" entity, allowing alumni members and non-members to communicate in virtually. This portal is Internet web-based systems that consist of interactive web page which is accessible exchanging information between user anywhere around the globe and web set without any time constraint. In addition, management in getting updated alumni record and resources by administrators could also be done via internet. This portal integrates several software packages and programming languages suitable for the development process. It is hope this portal would greatly benefit to all people who involve with it.